1998
DOI: 10.1038/bjc.1998.115
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation by semiquantitative reverse transcriptase polymerase chain reaction of MDR1, MRP and GSTp gene expression in breast carcinomas

Abstract: Summary Identification and quantitative evaluation of drug resistance markers are essential to assess the impact of multidrug resistance (MDR) in clinical oncology. The MDR1 gene confers pleiotropic drug resistance in tumour cells, but other molecular mechanisms are also involved in drug resistance. In particular, the clinical pattern of expression of the other MDR-related genes is unclear and their interrelationships are still unknown. Here, we report standardization of the procedures used to determine a reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 45 publications
1
12
2
Order By: Relevance
“…In the previous study, published in 1998, based on a series of 74 patients, we observed a significant positive correlation between MRP1 and GSTpi expression (Lacave et al, 1998). This correlation was not confirmed in the present study, possibly because of a more scattered distribution of expression levels.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…In the previous study, published in 1998, based on a series of 74 patients, we observed a significant positive correlation between MRP1 and GSTpi expression (Lacave et al, 1998). This correlation was not confirmed in the present study, possibly because of a more scattered distribution of expression levels.…”
Section: Discussioncontrasting
confidence: 98%
“…The conditions and methodological aspects of the end point rt -PCR procedures used in this study have been previously described in detail (Lacave et al, 1998). Although real-time PCR has been established as the gold standard rt -PCR procedure for gene expression studies since the end of the 1990s, most patients described here were included in the mid-1990s, at a time when real-time PCR was not routinely performed in the majority of laboratories.…”
Section: Rt-pcr Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive controls of specific gene expression were obtained with total RNA extracts from the HL60/DNR cell line for MDR1, 22 MCF7R cell line for MRP1, 23 human liver for MRP2 and MRP3, human lung for MRP4 and human skeletal muscle for MRP5. 7 Amplification of cDNA of ␤-actin, phospho-gluco kinase (PGK), and ␤ 2 -microglobulin (␤ 2 M) was used as an internal control for MDR1, MRP1 and MRP2-5, respectively.…”
Section: Rt-pcr Analysis Of Mdr1 and Mrps Expressionmentioning
confidence: 99%
“…Concerning MDR1 and MRP1 gene expression analysis, the RT-PCR method used has been already reported by our laboratory. 23 In order to check the accuracy of the RT-PCR method for MRP2-5 genes, PCR products of positive controls were sequenced on both strands using an ABI 310 genetic analyzer (PE Applied Biosystems, Inc., Courtaboeuf, France) and the BigDye Terminator sequencing kit (PE Applied Biosystems) according to the manufacturer's instructions. Sequence analysis using Sequence Analysis 2.1.1. software (PE Applied Biosystems) yielded the expected and previously published sequences (GenBank accession numbers U49248, AF083552, U83660 and U83661 for MRP2, MRP3, MRP4 and MRP5 genes, respectively).…”
Section: Rt-pcr Analysis Of Mdr1 and Mrps Expressionmentioning
confidence: 99%